Diagnosis of Small Intestinal Bacterial Overgrowth: Current Methods, Limitations, and Future Directions -a narrative literature review - Szymulewicz, Bartłomiej; Dąbrowski, Kacper; Podeszwa, Aleksandra; Łukaszewicz , Jakub; Niewęgłowska, Małgorzata; Walczak, Paulina; Bender, Aleksandra; Widomska, Katarzyna; Bernad, Mateusz; Krazińska, Oliwia; Gałach, Magdalena (Quality in Sport, 2026)
Background: Small intestinal bacterial overgrowth (SIBO) is a condition characterized by an abnormal alteration and/or increase in bacterial populations within the small intestine, leading to excessive carbohydrate fermentation and gas production. Clinical manifestations are nonspecific and include abdominal pain, bloating, diarrhea, and nutritional deficiencies. Despite increasing clinical recognition, accurate diagnosis remains challenging. Aim: To review currently available diagnostic methods for SIBO and evaluate their diagnostic accuracy and limitations. Material and methods: This study was conducted as a narrative literature review. A literature search was performed in the PubMed and Scopus databases. Systematic reviews, meta-analyses, original research articles, and clinical guidelines were included. The search was conducted using a combination of keywords including: “Small Intestinal Bacterial Overgrowth”, “SIBO”, “breath test”, “hydrogen breath test”, “methane breath test”, “small bowel aspirate”, “intestinal methanogen overgrowth”, and “SIBO diagnosis”. The literature screening and selection were performed independently by the authors. Studies published in languages other than English were excluded. No time restrictions were applied to the literature search. Results: Breath tests, particularly the glucose hydrogen breath test (GHBT) and lactulose hydrogen breath test (LHBT), are widely used due to their non-invasive nature and availability. However, their diagnostic accuracy remains limited. Small bowel aspirate remains the diagnostic gold standard but is invasive and methodologically limited. Conclusions:Current diagnostic methods for SIBO have significant limitations. Diagnostic results should therefore always be interpreted within the clinical context, highlighting the need for more accurate and standardized diagnostic approaches.